2021
DOI: 10.7759/cureus.18381
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Preoperative Neutrophil-Lymphocyte and Platelet-Lymphocyte Ratio in Determining the Stage of Colon Tumors

Abstract: IntroductionBiomarkers such as the neutrophil-lymphocyte ratio (NLR) and the platelet-lymphocyte ratio (PLR) are associated with the colon tumor stage and prognosis. Therefore, in our study, we investigated whether these biomarkers are important in determining the colon cancer stage. Materials and methodsThe outcomes in 268 patients operated on with the diagnosis of colon cancer between January 2011 and March 2019 were retrospectively analyzed. The relationship of the stage of the patients with the NLR or PLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…In recent years, there has also been many researchs about platelet indices and cancer diagnosis, and cancer stage (21). Yang-Yang Wu et al (22) found in their study about colorectal cancer MPV/PC was significantly different in subgroups between patients with stage I/II and stage III/IV cancer, and they believed that this ratio might be helpful in the differential diagnosis of early and advanced colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, there has also been many researchs about platelet indices and cancer diagnosis, and cancer stage (21). Yang-Yang Wu et al (22) found in their study about colorectal cancer MPV/PC was significantly different in subgroups between patients with stage I/II and stage III/IV cancer, and they believed that this ratio might be helpful in the differential diagnosis of early and advanced colorectal cancer.…”
Section: Discussionmentioning
confidence: 98%
“…It has also been questioned due to a potential limitation of stage migration in gastric cancer, and it has been suggested that the lymph node ratio be used to overcome this staging problem for patients with lymph node who have been studied in small numbers; the hypothesis is that the N-ratio may represent the true burden of lymph node metastases. 14 , 15 In a large cohort of conventional lymph node dissections, N-Ratio staging was found to be superior to AJCC TNM N-staging. 16 The N-ratio cut-off value in this study was 0.32.…”
Section: Discussionmentioning
confidence: 99%
“…Turhan et al [15], reported a significant relationship between NLR values and colorectal cancer stage and no significant relationship between PLR values and colorectal cancer stage. In the research of Rohit Krishna and Anil Kumar [16], NLR values increase according to the stage of colorectal cancer, from stage I to stage II to stage III, but NLR values at stage IV are lower than stage III.…”
Section: Patients Selectionmentioning
confidence: 97%